2019
DOI: 10.1177/2049936119886504
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive ceftaroline in combination with daptomycin or vancomycin for complicated methicillin-resistant Staphylococcus aureus bacteremia after monotherapy failure

Abstract: Background: Methicillin-resistant Staphylococcus aureus bacteremia (MRSA-B) may fail to improve with standard monotherapy, particularly in patients with multifocal infection, incomplete source control, or persistent bacteremia. Synergy observed in vitro between ceftaroline (CPT) and daptomycin (DAP) or vancomycin (VAN) may translate into clinical benefit. Here, we describe our experience with DAP/CPT and VAN/CPT for complicated MRSA-B after monotherapy failure. Methods: Single-center, retrospective review of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
0
22
5
Order By: Relevance
“…Additionally, engineering of the best hits provided a variant, L-11, with great potential to extend vancomycin’s spectrum against (MDR) Gram-negative pathogens. Synergies of vancomycin with other antimicrobials are well documented when targeting Gram-positive bacteria 30 32 , as well as its synergy in combination with outer-membrane perturbing (or not 33 ) antibiotics as colistins 34 , 35 . However, these combinations are still under study because of the relatively high toxicity observed 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, engineering of the best hits provided a variant, L-11, with great potential to extend vancomycin’s spectrum against (MDR) Gram-negative pathogens. Synergies of vancomycin with other antimicrobials are well documented when targeting Gram-positive bacteria 30 32 , as well as its synergy in combination with outer-membrane perturbing (or not 33 ) antibiotics as colistins 34 , 35 . However, these combinations are still under study because of the relatively high toxicity observed 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its only labeled indications being for aBSSSIs and CAP, ceftaroline has been used off-label for other MRSA infections, including infective endocarditis (IE). Ceftaroline has been linked to improved sterilization of blood when used with daptomycin in patients with MRSA IE versus daptomycin or vancomycin monotherapy [10]. Doses used in these case series are often higher than those studied in CANVAS/FOCUS trials, however, with sparse data on the safety and tolerability of increased dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin is a cyclic lipopeptide antibiotic with bactericidal activity against staphylococci, streptococci, and enterococci including VRE and MRSA [33]. It has different mechanisms of action including disruption of cell membrane function and inhibition of protein, DNA, and RNA synthesis.…”
Section: Daptomycinmentioning
confidence: 99%
“…Therefore, at least once-weekly CPK monitoring is required. Clearance of daptomycin is predominantly renal, and dosage adjustment is required when creatinine clearance is <30 mL/min [33,36].…”
Section: Daptomycinmentioning
confidence: 99%